1999
DOI: 10.1046/j.1365-3040.1999.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

The biochemical and molecular basis for photosynthetic acclimation to elevated atmospheric CO2

Abstract: There have been many recent exciting advances in our understanding of the cellular processes that underlie photosynthetic acclimation to rising atmospheric CO 2 concentration. Of particular interest have been the molecular processes that modulate photosynthetic gene expression in response to elevated CO 2 and the biochemical processes that link changes in atmospheric CO 2 concentration to the production of a metabolic signal. Central to this acclimation response is a reduction in ribulose-1,5-bisphosphate carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
325
3
13

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(364 citation statements)
references
References 142 publications
(210 reference statements)
23
325
3
13
Order By: Relevance
“…There are two basic 14 mechanisms by which Rubisco down-regulation occurs. The first mechanism 15 hypothesizes that the reduction in Rubisco content occurs as a consequence of the leaf C 16 build-up (Moore et al, 1999;Aranjuelo et al, 2008;. According to this 17 theory, when plants exposed to elevated CO 2 have limitations for increasing C sink 18 strength, plants decrease their photosynthetic rates to balance C source activity and sink 19 capacity (Aranjuelo et al, 2008;.…”
Section: Introductionmentioning
confidence: 99%
“…There are two basic 14 mechanisms by which Rubisco down-regulation occurs. The first mechanism 15 hypothesizes that the reduction in Rubisco content occurs as a consequence of the leaf C 16 build-up (Moore et al, 1999;Aranjuelo et al, 2008;. According to this 17 theory, when plants exposed to elevated CO 2 have limitations for increasing C sink 18 strength, plants decrease their photosynthetic rates to balance C source activity and sink 19 capacity (Aranjuelo et al, 2008;.…”
Section: Introductionmentioning
confidence: 99%
“…3A and B). Since there was no change in the enzyme activation state, our data revealed that the decreased initial and total Rubisco activity was the result of a depleted Rubisco protein content (Moore et al, 1999). The fact that WD plants exposed to elevated CO 2 had depleted Rubisco and TSP contents, and a larger TSS value suggests that those plants had problems to increase sink strength (reflected by the lack of CO 2 effect on DM production).…”
Section: Discussionmentioning
confidence: 73%
“…TSS data (Table 3) confirmed that plants exposed to elevated CO 2 , especially in WD plants, had a massive production and build-up of carbohydrates. Carbon sink/source imbalance induced photosynthetic acclimation caused by depletions in the expression of Calvin cycle enzymes (Moore et al, 1999;Stitt and Krapp, 1999;Aranjuelo et al, 2005b;Reich et al, 2006;Rogers et al, 2006). However, it should also be noted that all the enzymes involved in the photosynthetic processes may not be equally affected by enhanced CO 2 (Moore et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid development of plant molecular techniques aided our understanding of the acclimatization of plants to elevated [C0 2 ] (Moore et al, 1999 Abbreviations: CA, carbonic anhydrase; [C0 2 J, CO 2 concentration; control leaves, flag-leaf blades of control plants; cFBP, cytosolic fructose-l,6-bisphosphatase; DAT, days after transplanting; high-C0 2 -grown leaves, flag-leaf blades of rice plants grown under elevated CO 2 concentration; P=probability level; rubisco, ribulose-l,5-bisphosphate carboxylase/oxygenase; SDS, sodium dodecyl sulfate; SLA, specific leaf area; SPS, sucrose-phosphate synthase; SSU, small subunit of ribulose-l,5-bisphosphate carboxylase/oxygenase; stems, culms and leaf sheaths.…”
mentioning
confidence: 99%